(untitled) (Medico Legal Update, 2021)
Objective: The aim of this review is to critically assess three decades (1989 to 2019) of breast cancer research in Yemen and to identify the gaps in, and need for, breast cancer research in Yemen. Methodology: A search was performed in Web of Science, EMBASE, PubMed, Google Scholar and Ovid to identify articles on breast cancer research in Yemen that were published in the last three decades. The articles were selected and reviewed by experts in this field, based on clinical relevance and future research implications. Results: This review comprised 19,031 participants, extracted from 27 articles that were included and analyzed. Breast cancer patients in Yemen were commonly diagnosed at an early age of 50 years or younger. Overall, awareness of breast cancer among Yemeni women was very poor. Some studies reported that a low rate of only 11%-17.4% of Yemeni women practiced breast screen examination. Only 1.6% of the Yemeni women had been screened by a mammogram test. The highest performed surgery was a modified radical mastectomy (N=211). The highest cases of breast cancer were reported in Hadramout (N=956) and the most common histological subtype was invasive ductal carcinoma (N=2695). Conclusions: Yemen is characterised by three decades of scattered, fragmented and poor quality breast cancer research. Therefore, there is a need to establish a breast cancer research center in Yemen to research all aspects of breast cancer in Yemen, and to build bridges for collaborations in breast cancer research globally.